2020
DOI: 10.21203/rs.3.rs-28937/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflammation is Correlated with Abnormal Functional Connectivity in Unmedicated Bipolar Depression: A Resting State FMRI Study

Abstract: Objectives Inflammation might play a role in bipolar disorder (BD), but it remains unclear the relationship between inflammation and brain structural and functional abnormalities in patients with BD. In this study, we focused on the alterations of functional connectivity (FC), peripheral pro-inflammatory cytokines and their correlations to investigate the role of inflammation in FC in BD depression.Methods In this study, 42 unmedicated patients with BD II depression and 62 healthy controls (HCs) were enrolled.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Overall, most studies showed that the expression levels of proinflammatory cytokines, such as IL-1β, IL-6, TNF-α, IL-8, IL-17, IL-18, and IFN-γ, and anti-inflammatory cytokines IL-10 and IL-1RA are elevated in patients with BD. 5 , 22 – 44 Inconsistent results on IL-4 level have been obtained for patients with BD, whereas consistent results have been derived from studies on IL-1β, IL-6, and TNF-α. 5 , 6 , 24 , 25 , 27 , 32 41 , 45 After BD medication, the expression of proinflammatory cytokines IL-1β, IL-6, and TNF-α decreases, whereas the expression of anti-inflammatory cytokines IL-4 and IL-10 increases.…”
Section: Relationship Between Bd and Different Inflammatory Cytokinesmentioning
confidence: 94%
See 1 more Smart Citation
“…Overall, most studies showed that the expression levels of proinflammatory cytokines, such as IL-1β, IL-6, TNF-α, IL-8, IL-17, IL-18, and IFN-γ, and anti-inflammatory cytokines IL-10 and IL-1RA are elevated in patients with BD. 5 , 22 – 44 Inconsistent results on IL-4 level have been obtained for patients with BD, whereas consistent results have been derived from studies on IL-1β, IL-6, and TNF-α. 5 , 6 , 24 , 25 , 27 , 32 41 , 45 After BD medication, the expression of proinflammatory cytokines IL-1β, IL-6, and TNF-α decreases, whereas the expression of anti-inflammatory cytokines IL-4 and IL-10 increases.…”
Section: Relationship Between Bd and Different Inflammatory Cytokinesmentioning
confidence: 94%
“… 5 , 22 – 44 Inconsistent results on IL-4 level have been obtained for patients with BD, whereas consistent results have been derived from studies on IL-1β, IL-6, and TNF-α. 5 , 6 , 24 , 25 , 27 , 32 41 , 45 After BD medication, the expression of proinflammatory cytokines IL-1β, IL-6, and TNF-α decreases, whereas the expression of anti-inflammatory cytokines IL-4 and IL-10 increases. 46 – 56 The relationship between BD symptomatic improvement after drug treatment and the variation trends of pro/anti-inflammatory cytokine levels suggests a connection between immune inflammation and BD.…”
Section: Relationship Between Bd and Different Inflammatory Cytokinesmentioning
confidence: 94%